Knowledge, Awareness, and Compliance of Disease Surveillance and Notification Among Jordanian Physicians in Residency Programs - Nansi Abdulrahim MD; Ihab Alasasfeh MSc; Yousef S. Khader ScD; Ibrahim Iblan MD (SAGE Publishing, 2019)
Health professionals' knowledge and awareness of the disease surveillance is essential for reporting diseases to health departments. This study aimed to assess the knowledge and attitudes of Jordanian physicians toward public health surveillance of communicable disease. A cross-sectional study was conducted among resident doctors who were working in 4 main Ministry of Health hospitals and 2 teaching hospitals in Jordan in September 2017. A self-administered paper-based questionnaire was used to collect the data. The questionnaire collected information about sociodemographic and practice-related characteristics of physicians and included items to assess their knowledge of surveillance and reporting practices. This study included 223 physicians (152 males and 71 females). About 60.1% of the residents were graduates from medical schools in Jordan and the remaining (39.9%) were graduates from medical schools in other countries. Approximately two thirds of residents (62.3%) were doing their residency in Ministry of Health hospitals and the rest (37.7%) in 2 teaching hospitals. Only 44.8% of physicians had defined surveillance correctly. Only 27.4% of physicians had been educated or trained on surveillance. About 39.5% of physicians had filled at least one report form during their practice. The main reasons for not reporting mandatory diseases were high workload (49.8%) and being not trained on reporting diseases (46.6%). A relatively high percentage of physicians have insufficient knowledge of surveillance and reporting of notifiable communicable diseases. Training of physicians on surveillance and diseases notification is highly needed. The practice of disease notification should be enforced in Jordanian hospitals.